Benthic fluxes of dissolved silica are an important component of the marine Si cycle in the coastal zone. (31st August 2022) - Borawska, Zuzanna; Szymczycha, Beata; Silberberger, Marc J.; Koziorowska-Makuch, Katarzyna; Szczepanek, Marta; Kędra, Monika
Abstract: Spatial and seasonal changes in benthic fluxes of dissolved silica (DSi) across the coastal zones were investigated in the southern Baltic Sea. Measurements were performed using ex situ incubations of sediment cores with natural benthic assemblages. Obtained benthic fluxes ranged from the uptake of −1.11 mmol m −2 d −1 in summer to a release of 6.79 mmol m −2 d −1 in autumn, while in situ concentrations in the bottom water were the lowest in autumn (1 μmol L −1 ) and the highest in winter (up to 58 μmol L −1 ). Sediments with high mud content had the highest fluxes in autumn, intermediate in spring, and the lowest in winter whereas no clear seasonal patterns were detected for sandy sediments. Generalized Linear Models indicated that in shallow enclosed areas biological factors, particularly presence of Chironomidae larvae, explained DSi fluxes variation while in open areas the environmental factors, such as organic matter quantity and quality, were key explanatory variables. In all studied environments (enclosed lagoon, open bay, and open coastal zone) DSi benthic fluxes represent an important component of the marine Si cycle. Further, the total yearly load of DSi from two major rivers (Vistula and Oder) and from the sediments, to the southern Baltic Sea reaches 258 kt y −1 of which benthic fluxes may constitute up to 34%. Graphical abstract: Image 1 Highlights: Spatial and seasonal changes in dissolved silica benthic fluxes were investigated. There were significant differences in fluxes rates between sands and sandy muds. Biological factors controlled benthic fluxes in the shallow enclosed areas. Environmental factors mainly explained flux variation in the open-sea areas. Benthic fluxes constitute a significant part of silica budget in the coastal areas.